The Effect of Fundamental Knowledge of Mathematics on Diploma UTHM Student’s Performance in Physics - Nur Adriana Sofea Ahmad Nor; Nur Baiti Janna Nor Azmi; Sazeli, Zul Afiq (Multidisciplinary Applied Research and Innovation, 2024)
Physics is a study of nature that deals with the structure of matter and its interactions. The basics of physics include experiments, observation and the analysis of the phenomena using mathematical and computational methods. Fundamental knowledge of mathematics can significantly affect a student’s performance in physics. Comprehending the mathematical descriptions is necessary to thoroughly comprehend physics principles. The mathematics and physics results obtained from Year 2 DAU student did not explain any significant relationship. The objective of this study is to determine the level of performance of students in physics according to the level of UTHM students’ Diploma achievement in mathematics, to identify how Diploma UTHM students perform in physics on their conceptual understanding of mathematics and to determine the effects of math problem-solving skills on Diploma UTHM students’ physics performance. The sample size is determined by using the Krejcie and Morgan sampling method. Descriptive analysis was used to analyse the research questions and correlation analysis using SPSS was used for hypothesis testing to interpret the research output; the result of SPM mathematics and final exam Physics, their opinion about conceptual understanding and the cognitive tools used to answer physics questions. The result of this research indicates that there is a significant relationship between mathematics results in physics correlate at 0.366 with a significant level below 1%. Hence, the relationship between mathematics and physics can be explained by using correlation analysis and students’ results are expected to be better hereafter.